A Parade of Lines - Holmes, Paul C.; Lehman, Anita J. (San Fransisco Canfield Press, 1971)
In a world seemingly filled with unending contradictions and monumental problems, young people must be encouraged to believe there is a possibility for change. This book hopes to expose students, through literature and essays, to provacative ideas and problems in a positive manner.
Keywords: Literature